NATIONAL DEMOCRATIC PARTY OF GERMANY IN THE CONTEXT OF ELECTORAL PREFERENCES’ RADICALIZATION - Гримська, М. І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The peculiarities of far right political parties in Germany after World War II are outlined. Main stages of their evolution are identified and each of them is characterized in details. The establishment of the National Democratic Party of Germany is described, its place in the party system is presented, and ideology and values are characterized.